Brainstem variant of posterior reversible encephalopathy syndrome: A case report. Issue 6 (December 2015) - Tortora, Fabio; Caranci, Ferdinando; Belfiore, Maria Paola; Manzi, Francesca; Pagliano, Pasquale; Cirillo, Sossio
Posterior reversible encephalopathy syndrome (PRES) is a clinico-radiological condition, generally observed in conjunction with severe and acute hypertension, that involves mainly the posterior head areas (occipital and temporal lobes) and anterior "watershed" areas. In this syndrome it is rare to observe a predominant involvement of the brainstem. We describe the clinical and radiological findings in a patient with brainstem involvement, discussing its pathophysiological features and possible differential diagnosis.